The Impact of the Implementation of the International Baccalaureate (IB) Curriculum on Shaping the Quality of Teacher Performance at Islamic Village Tangerang School - Nada Shofa Lubis; M. Syadeli Hanafi; Sholeh Hidayat (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The International Baccalaureate (IB) curriculum has emerged as a preferred global education framework in many schools worldwide. It not only emphasizes academic achievement but also fosters essential skills for success in an increasingly interconnected global society. This study aims to analyze the impact of implementing the IB curriculum on the quality of teacher performance. Employing a mixed-methods approach with a qualitative focus supported by quantitative data, the study involved 58 teachers from Islamic Village schools: 17 kindergarten, 29 elementary, 6 junior high, and 6 senior high school teachers, with no age restrictions. Data were collected through questionnaires and document analysis, and analyzed using descriptive qualitative methods. The findings indicate that the implementation of the IB curriculum significantly enhances various aspects of teacher performance: teaching ability (88.90%), understanding of subject matter (90.62%), student interaction (89.74%), classroom management (90.07%)—all rated as